Ball-milled Ni2P/g-C3N4 for improved photocatalytic hydrogen production. (12th May 2023) - Xiao, Yutong; Wang, Ziqun; Li, Longfeng; Gu, Quan; Xu, Man; Zhu, Li; Fu, Xianliang
Abstract: Transition metal phosphides (TMPs) are ideal candidates to replace precious cocatalysts for photocatalytic hydrogen evolution reaction (HER). Understanding the structure-activity relationships between TMPs and the host photocatalysts is an important criterion for the development of highly active TMPs for HER. In this work, the relations were explored with Ni2 P and g-C3 N4 as prototypes. Ni2 P with a clear composition and structure was prepared first by a mild solvothermal method and was then loaded on g-C3 N4 with an exact content through a ball milling process. The effects of the modification of Ni2 P on g-C3 N4 structure, absorption, texture, HER activity, and photo-electrochemical properties were investigated. The results demonstrated that the crystal structure and the texture of g-C3 N4 are less impacted by the decoration of Ni2 P, but the HER activity can be substantially improved. g-C3 N4 modified with 3% Ni2 P showed the highest HER performance and it is ca. 9 times higher than the pristine g-C3 N4 even Ni2 P was loaded just by a simple ball milling process. Ni2 P played a dual role as trapping sites to capture photoinduced electrons and the reactive centers to trigger the evolution of hydrogen for its high work function and the low HER overpotential. This work reveals some reliable structure-activity relationships between Ni2 P and g-C3 N4 and offers a simple approach to synthesize highly efficient Ni2 P and its loading on host photocatalyst for enhanced HER. Graphical abstract: Image 1 Highlights: New phosphidation process was developed to fabricate highly crystallized Ni2 P. Ball-milling g-C3 N4 with Ni2 P could boost the photocatalytic HER activity. The structure-activity relationships between Ni2 P and g-C3 N4 was explored. Ni2 P played a dual role as e − -trapping centers and reactive sites to trigger HER.